Acceptance Procedure and Storage of Goods Inventory at Swiss-Belhotel Harbour Bay Batam - Anjelina Anjelina; Muhammad Amri (Pusat P2M Politeknik Negeri Batam, 2016)
The final task is done in Store Keeper Swiss-Belhotel Harbour Bay Batam. The company is engaged in hotel services and pariwisata.Penelitian aims to determine how the application procedure goods receipt and storage of supplies made by Swiss-Belhotel Harbour Bay. What is the cause of the acceptance procedures and storage of supplies were inadequate, and how the solutions to overcome them. The method used in this study were interviews with those involved in the reception and storage of goods procedure to fix the flowchart. The evaluation of the reception and storage procedures are good enough, it's just still a lack of employees in the department storage/ warehouse and separation of functions between departments Receiving and Store Keeper that there are functions for control duties effectively in the work.